2016
DOI: 10.7150/ijms.14579
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the receptor activator of nuclear factor-kB ligand in peripheral blood mononuclear cells in patients with acute Charcot neuroarthropathy

Abstract: Introduction. The receptor activator of nuclear factor-kB (RANK), ligand (RANK-L) and osteoprotegerin (OPG) are implicated in the pathogenesis of acute Charcot neuroarthropathy (CN).Materials and Methods. This study aimed to investigate the expression of RANK-L and OPG in peripheral blood mononuclear cells (PBMC) from patients with acute CN.Results. We found that the expression of RANK-L was lower in patients with acute CN as compared with diabetic control subjects and healthy control participants; whereas OPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, in acute DNOAP, the local inflammatory response related to increased pro-inflammatory cytokine secretion is not associated with a systemic inflammatory syndrome [ 40 ]. Bergamini et al [ 41 ] reported that the RANKL expression was significantly lower in the peripheral blood mononuclear cells of acute DNOAP patients than that in normal and diabetic controls and the RANKL expression increased at the time of healing compared with the values of acute phase. Their data suggested the existence of compensatory immunoregulatory mechanisms to potentially limit bone resorption during acute DNOAP.…”
Section: Pathogenesismentioning
confidence: 99%
“…However, in acute DNOAP, the local inflammatory response related to increased pro-inflammatory cytokine secretion is not associated with a systemic inflammatory syndrome [ 40 ]. Bergamini et al [ 41 ] reported that the RANKL expression was significantly lower in the peripheral blood mononuclear cells of acute DNOAP patients than that in normal and diabetic controls and the RANKL expression increased at the time of healing compared with the values of acute phase. Their data suggested the existence of compensatory immunoregulatory mechanisms to potentially limit bone resorption during acute DNOAP.…”
Section: Pathogenesismentioning
confidence: 99%
“…Pathways that have received the most attention in the pathogenesis of CN include the receptor activator of nuclear factor-jB, receptor activator of nuclear factor-jB ligand and osteoprotegerin 11 , and more recently, abnormalities in sclerostin, dickkopf-1, Wnt inhibitory factor-1 and Wnt ligand-1 12 . The role of these pathways is complex, with a recent study showing initial suppression of receptor activator of nuclear factor-jB ligand in peripheral blood mononuclear cells followed by increased levels in those with faster healing on magnetic resonance imaging 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Corneal confocal microscopy (CCM) is a rapid non-invasive ophthalmic imaging technique, which allows high-resolution imaging of corneal nerves. We have pioneered its use to identify axonal loss in diabetic 21,22 and other peripheral neuropathies 23,24 , and have shown that it has a very high sensitivity and specificity for identifying diabetic autonomic neuropathy 13 . Furthermore, we have recently shown a rapid decline in corneal nerve fibers, with no change in neurophysiology or quantitative sensory testing, before the development of CN in a patient with diabetes; suggesting that small fiber neuropathy might be critical in the development of CN 25 .…”
Section: Introductionmentioning
confidence: 99%
“…A small study by Bergamini et al 28 in 2016 provided potentially conflicting data by demonstrating significantly decreased levels of RANKL in circulating peripheral blood monocytes from patients with acute CNA compared with controls. They found that increased levels of circulating RANKL coincided with clinical resolution and suggested that there is a local compensatory mechanism in acute CNA which limits bone remodelling.…”
Section: Introductionmentioning
confidence: 99%